Public administration as a catalyst for cluster development - Kaźmierski, Jan (Journal of Public Governance, 2013)
Clusters are perceived as accelerator of progress and competitiveness. Thus, the stimulation of their development has become a significant element of EU countries’ policy. The selection of proper instruments that support cluster development poses a peculiarly significant problem. In Poland for a couple of years clusters have become the object of special interest of public authorities of different levels as well. Validity of public administration getting engaged in cluster initiatives’ development is undisputed. Principally it should consist in the stimulation of business environment to take up various forms of cooperation and creation of proper support instruments. In regional policy it plays a strictly qualitative role. However, although this problem has been given a high rank, Polish policy faces numerous restrictions here. The goals set in the article are of both cognitive and practical – based on empirical studies – nature. Illustrating assumptions, models and prerequisites of the policy of cluster development support as well as depicting programs and instruments of regional policy represent the cognitive goals. Practical purposes focus on roles and tasks of public authorities in relation to the process of cluster development. To conduct empirical studies, the author used primary sources employing diverse investigational techniques. The majority of crucial findings can be applied to the examined region as well as to the other regions of the country.